EFFECT OF HARVESTING STAGES AND PERFORATED PACKAGES ON THE QUALITY AND STORAGE LIFE OF STRAWBERRY FRUIT - Ijaz Akhtar; Abdur Rab (Journal of Animal and Plant Sciences, 2020)
A study was done to investigate the effects of harvest stage and perforated packaging on fruit quality and storage in strawberry. Fruit were harvested at three stages of maturity, including the pink, red, and dark red stages, and were stored for 8 days at 5±2°C and 90% RH. The fruit was either unpackaged during storage (control) or stored inside plastic packages that had 12, 18, or 24 circular perforations (0.5cm diameter). Fruit harvested at the dark red stage had the greatest weight loss, total soluble solids (TSS), total sugars, reducing sugars, and sugar/acid ratio, the least number of marketable fruit, the shortest shelf life, and the lowest amount of non-reducing sugars, titratable acidity, moisture content, and ascorbic acid content. In contrast, fruit harvested at the red stage had the greatest number of marketable fruit, the least weight loss, TSS, total sugars, and reducing sugars, and the lowest sugar/acid ratio. Packaging significantly affected fruit storage and quality and was best when fruits were harvested at the red stage and stored in packages with18 perforations.
Keywords: Ascorbic acid; plastic packaging; titratable acidity; total soluble solids; shelf life